Long-term mechanical performance of marine sediments solidified with cement, lime, and fly ash. Issue 1 (2nd January 2018) - Wang, Dongxing; Zentar, Rachid; Abriak, Nor Edine; Di, Shengjie
ABSTRACT: Most of the previous studies concerning solidification of marine sediments focus mainly on the mechanical properties within the curing time of 90 days, but the long-term (e.g., 360 days) behavior has not been fully appreciated. The current study attempts to address this issue by analyzing the long-term strength and deformation behavior of sediments solidified with cement, lime, and fly ash. A series of unconfined compressive tests were conducted, and the effect of binder amount and binder type is discussed on 360-day cured specimens. It can be found that the increasing amount of cement/lime enhances the mechanical performance of sediments. The fly ash addition plays different roles in cement- and lime-solidified sediments. Fly ash improves the strength and modulus of lime-solidified sediments but weakens the mechanical characteristics of cement-solidified sediments. The test results demonstrate that the lime–fly ash binder is capable of replacing lime and cement–fly ash binder for sediment solidification from the viewpoint of economical cost and good ability to gain strength. The relationships of compressive strength vs. deformation modulus, compressive strength vs. failure strain, and compressive strength vs. tensile strength are quantitatively derived on 360-day cured specimens. The scanning electron microscope image analysis reveals the intrinsic microstructural mechanisms of improvement in the long-term mechanical performance of sediments due to the addition of chemical binders.